Rest versus Exercise Hemodynamics for Middle Cerebral Artery Aneurysms: A Computational Study - Bowker, T.J.; Watton, P.N.; Summers, P.E.; Byrne, J.V.; Ventikos, Y. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Exercise is an accepted method of improving cardiovascular health; however, the impact of increases in blood flow and heart rate on a cerebral aneurysms is unknown. This study was performed to simulate the changes in hemodynamic conditions within an intracranial aneurysm when a patient exercises. MATERIALS AND METHODS: Rotational 3D digital subtraction angiograms were used to reconstruct patient-specific geometries of 3 aneurysms located at the bifurcation of the middle cerebral artery. CFD was used to solve for transient flow fields during simulated rest and exercise conditions. Inlet conditions were set by using published transcranial Doppler sonography data for the middle cerebral artery. Velocity fields were analyzed and postprocessed to provide physiologically relevant metrics. RESULTS: Overall flow patterns were not significantly altered during exercise. Across subjects, during the exercise simulation, time-averaged WSS increased by a mean of 20% (range, 4%–34%), the RRT of a particle in the near-wall flow decreased by a mean of 28% (range, 13%–40%), and time-averaged pressure on the aneurysm wall did not change significantly. In 2 of the aneurysms, there was a 3-fold order-of-magnitude spatial difference in RRT between the aneurysm and surrounding vasculature. CONCLUSIONS: WSS did not increase significantly during simulated moderate aerobic exercise. While the reduction in RRT during exercise was small in comparison with spatial differences, there may be potential benefits associated with decreased RRT (ie, improved replenishment of nutrients to cells within the aneurysmal tissue). ARaspect ratiobpmbeats per minuteCFDcomputational fluid dynamicsECendothelial cellmaxmaximumminminimumMMPmatrix metalloproteinaseOSIoscillatory shear indexPC-MRAphase-contrast MR angiographyPIpulsatility indexReReynolds numberRRTrelative residence timeSIMPLECsemi-implicit method for pressure-linked equations consistentTtime periodVvelocityWSSwall shear stress